2008
DOI: 10.1038/bmt.2008.108
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation for children with acute lymphoblastic leukemia

Abstract: EFS for children with ALL continues to increase and is predicted to reach 90% with current therapy. Better understanding of leukemia cell biology and pharmacogenetics has led to the design of more effective treatment and also refined the prognostic features associated with a poor outcome. ALL characterized by the translocation t(9;22) or t(4;11), or by a hypodiploid karyotype or by an incomplete response to induction therapy is likely to relapse. SCT for ALL is largely used to treat patients failing primary ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, most recent COG study failed to show an advantage of HSCT over chemotherapy [136], while Interfant-99 study showed that the benefit was restricted to a very high-risk subgroup with 2 additional unfavorable prognostic features: age <6 months and either poor response to steroids or leukocyte count ≥ 300 x 10 9 /L [137]. Similarly, somewhat ambiguous results have been reported from studies that attempt to compare EFS after transplant or chemotherapy for children with hypodiploid ALL [138], poor early responders [99,139], persistent MRD, and high-risk T-cell ALL [140,141]. Overall, there is no absolute indication for HSCT in children with ALL in CR1.…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…However, most recent COG study failed to show an advantage of HSCT over chemotherapy [136], while Interfant-99 study showed that the benefit was restricted to a very high-risk subgroup with 2 additional unfavorable prognostic features: age <6 months and either poor response to steroids or leukocyte count ≥ 300 x 10 9 /L [137]. Similarly, somewhat ambiguous results have been reported from studies that attempt to compare EFS after transplant or chemotherapy for children with hypodiploid ALL [138], poor early responders [99,139], persistent MRD, and high-risk T-cell ALL [140,141]. Overall, there is no absolute indication for HSCT in children with ALL in CR1.…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%